2007
DOI: 10.1002/eji.200737033
|View full text |Cite|
|
Sign up to set email alerts
|

TGF‐β regulates pathology but not tissue CD8+ T cell dysfunction during experimental Trypanosoma cruzi infection

Abstract: Infection with the protozoan parasite Trypanosoma cruzi leads to chronic infection, with parasite persistence primarily in muscle tissue. CD8 + T cells isolated from muscle tissue of T. cruzi-infected mice display decreased production of IFN-c in response to T cell receptor engagement. The expression of TGF-b at the site of CD8 + T cell dysfunction and parasite persistence suggested that this immunoregulatory cytokine might play a role in these processes. Mice expressing a T cell-specific dominant negative TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 37 publications
1
31
0
2
Order By: Relevance
“…TGF-β is a pivotal regulator of inflammation during the acute phase of experimental Chagas disease, as shown from the extensive work performed by Silva et al 21 and Gutierrez et al 27 and as reviewed. 20,44 TGF-β is produced during the first week postinfection and constantly throughout the acute and chronic phases in both monkey 45 and mouse 46,47 models. The final outcome depends on multiple factors such as parasite virulence and pathogenicity, coinfection with different T. cruzi clones, and intensity of anti-inflammatory responses induced by T. cruzi molecules via an increase in systemic and local TGF-β levels.…”
Section: Review Implication Of Tgf-β In Cardiac Complications Of Chagmentioning
confidence: 99%
“…TGF-β is a pivotal regulator of inflammation during the acute phase of experimental Chagas disease, as shown from the extensive work performed by Silva et al 21 and Gutierrez et al 27 and as reviewed. 20,44 TGF-β is produced during the first week postinfection and constantly throughout the acute and chronic phases in both monkey 45 and mouse 46,47 models. The final outcome depends on multiple factors such as parasite virulence and pathogenicity, coinfection with different T. cruzi clones, and intensity of anti-inflammatory responses induced by T. cruzi molecules via an increase in systemic and local TGF-β levels.…”
Section: Review Implication Of Tgf-β In Cardiac Complications Of Chagmentioning
confidence: 99%
“…Photographs were taken using a Nikon Eclipse TE2000-U inverted microscope using a 40ϫ objective. Inflammation was evaluated semiquantitatively on lowpower microscopic examination, according to the distribution and extent of inflammatory cells (focal, confluent, or diffuse) in epicardium and myocardium (1ϩ for a single inflammatory foci, 2ϩ multiple nonconfluent foci of inflammatory infiltrate, 3ϩ for confluent inflammation, and 4ϩ for diffuse inflammation extended throughout the section) (30,31). Furthermore, it also assessed enlarged endothelial cells, perivascular edema, and disrupted and necrotic myocardial fibers.…”
Section: Materials (I) Drugsmentioning
confidence: 99%
“…Several studies have demonstrated that TGF-␤ plays a major role in the establishment and pathogenesis of T. cruzi infection (reviewed in reference 2). TGF-␤ plays a crucial role in three important processes associated with Chagas' disease: (i) stimulation of fibrosis, as demonstrated in Chagas' disease patients and experimental animal models (1,31); (ii) parasite cellular invasion and proliferation (10,18,32,34); (iii) downregulation of cellular and immune mechanisms of parasite control (15,27,28). Moreover, significantly higher circulating levels of TGF-␤1 have been observed in patients with Chagas' disease cardiomyopathy (1).…”
mentioning
confidence: 99%